Current state of and needs for hepatitis B screening: results of a large screening study in a low-prevalent, metropolitan region. - Julie Bottero (Public Library of Science (PLoS), 2014)
Background In low hepatitis B virus (HBV)-prevalent countries, most HBV-infected persons are unaware of their status. We aimed to evaluate whether (i) previous HBV-testing, (ii) physicians decision to screen, and (iii) CDC's recommendations identified infected individuals and which risk-factor groups needing testing. Methods During a mass, multi-center HBV-screening study from September 2010-August 2011, 3929 participants were screened for hepatitis B surface antigen (HBsAg), anti-HBs and anti-Hepatitis B core antibodies (anti-HBcAb). Questions on HBV risk-factors and testing practices were asked to participants, while participants' eligibility for HBV-testing was asked to study medical professionals. Results 85 (2.2%) participants were HBsAg-positive, while 659 (16.8%) had either resolved HBV infection or isolated anti-HBcAb. When comparing practices, HBV-testing was more likely to occur in HBV-infected participants if Centers for Disease Control and Prevention (CDC) recommendations were used (Sensitivity = 100%, 95%CI: 95.8-100) than physicians' discretion (Sensitivity = 87.1%, 95%CI: 78.0-93.4) or previous HBV-test (Sensitivity = 36.5%, 95%CI: 26.3-47.6) (p<0.0001). Nevertheless, many non-infected individuals would still have been screened using CDC-recommendations (Specificity = 31.1%, 95%CI: 29.6-32.6). Using multivariable logistic regression, HBsAg-positive status was significantly associated with the following: males, originating from high HBV-endemic region, contact with HBV-infected individual, without national healthcare, and intravenous-drug user (IDU). Of these risk-factors, physician's discretion for testing HBV was not significantly associated with participants' geographical origin or IDU. Conclusions Missed opportunities of HBV-screening are largely due to underestimating country of origin as a risk-factor. Applying CDC-recommendations could improve HBV-screening, but with the disadvantage of many tests. Further development of HBV-testing strategies is necessary, especially before severe disease occurs.